New Insight on the Cytoprotective/Antioxidant Pathway Keap1/Nrf2/HO-1 Modulation by Ulva intestinalis Extract and Its Selenium Nanoparticles in Rats with Carrageenan-Induced Paw Edema - May Almukainzi; Thanaa A. El-Masry; Hend Selim; Asmaa Saleh; Mostafa El-Sheekh; Mofida E. M. Makhlof; Maisra M. El-Bouseary (Marine Drugs, 2023)
Currently, there is growing interest in exploring natural bioactive compounds with anti-inflammatory potential to overcome the side effects associated with the well-known synthetic chemicals. Algae are a rich source of bioactive molecules with numerous applications in medicine. Herein, the anti-inflammatory effect of Ulva intestinalis alone or selenium nanoparticles loaded with U. intestinalis (UISeNPs), after being fully characterized analytically, was investigated by a carrageenan-induced inflammation model. The pretreated groups with free U. intestinalis extract (III and IV) and the rats pretreated with UISeNPs (groups V and VI) showed significant increases in the gene expression of Keap1, with fold increases of 1.9, 2.27, 2.4, and 3.32, respectively. Similarly, a remarkable increase in the Nrf2 gene expression, with 2.09-, 2.36-, 2.59-, and 3.7-fold increases, was shown in the same groups, respectively. Additionally, the groups III, IV, V, and VI revealed a significantly increased HO-1 gene expression with a fold increase of 1.48, 1.61, 1.87, and 2.84, respectively. Thus, both U. intestinalis extract and the UISeNPs boost the expression of the cytoprotective/antioxidant pathway Keap1/Nrf2/HO-1, with the UISeNPs having the upper hand over the free extract. In conclusion, U. intestinalis and UISeNPs have proven promising anti-inflammatory activity through mediating different underlying mechanisms.